Complete genome sequences of two strains of Treponema pallidum subsp. pertenue from Ghana, Africa: Identical genome sequences in samples isolated more than 7 years apart. - Michal Strouhal; Lenka Mikalová; Pavla Havlíčková; Paolo Tenti; Darina Čejková; Ivan Rychlík; Sylvia Bruisten; David Šmajs (Public Library of Science (PLoS), 2017)
Treponema pallidum subsp. pertenue (TPE) is the causative agent of yaws, a multi-stage disease, endemic in tropical regions of Africa, Asia, Oceania, and South America. To date, four TPE strains have been completely sequenced including three TPE strains of human origin (Samoa D, CDC-2, and Gauthier) and one TPE strain (Fribourg-Blanc) isolated from a baboon. All TPE strains are highly similar to T. pallidum subsp. pallidum (TPA) strains. The mutation rate in syphilis and related treponemes has not been experimentally determined yet.Complete genomes of two TPE strains, CDC 2575 and Ghana-051, that infected patients in Ghana and were isolated in 1980 and 1988, respectively, were sequenced and analyzed. Both strains had identical consensus genome nucleotide sequences raising the question whether TPE CDC 2575 and Ghana-051 represent two different strains. Several lines of evidence support the fact that both strains represent independent samples including regions showing intrastrain heterogeneity (13 and 5 intrastrain heterogeneous sites in TPE Ghana-051 and TPE CDC 2575, respectively). Four of these heterogeneous sites were found in both genomes but the frequency of alternative alleles differed. The identical consensus genome sequences were used to estimate the upper limit of the yaws treponeme evolution rate, which was 4.1 x 10-10 nucleotide changes per site per generation.The estimated upper limit for the mutation rate of TPE was slightly lower than the mutation rate of E. coli, which was determined during a long-term experiment. Given the known diversity between TPA and TPE genomes and the assumption that both TPA and TPE have a similar mutation rate, the most recent common ancestor of syphilis and yaws treponemes appears to be more than ten thousand years old and likely even older.